Gender stereotypes in the coach-matching process: a case of male executives in Nigeria - Anya, Tshidi (My University, 2017)
The expected economic growth in Africa and, in particular within Nigeria, (Ogunlesi, 2014) opens doors to more global business opportunities. This growth within the African continent also contributes towards the growth of organisational developmental practices such as executive coaching. This is because executive coaching is undoubtedly one of the fastest developmental interventions used by organisations worldwide (Bartlett, 2006). For that reason, it is imperative for organisations within the Nigerian business setting, where most executives are males, to understand possible inhibitors that could affect the formation of a coaching relationship between male executives and coaches from a different gender. Previous research on the impact of gender in a coaching relationship has found that gender plays a role when matching executives with coaches (Gray & Goregaokar, 2010). It has also been found that gender similarity of the coach and the executive increases self-awareness of the executives (Bozer, Joo & Santora, 2015). Boyce, Jackson and Neal (2010) advocate that when there is gender commonality between coaches and executives; rapport and trust are established much quicker. Therefore the main purpose of this research is to understand the role that gender and in particular, how gender stereotypes could affect the coach-matching process between female coaches and male executives in a patriarchal society like Nigeria (Nwosu, 2012). A qualitative approach was implored to uncover trends in thoughts and opinions of the participants. The researcher sought in-depth understanding of the participants and their experiences. A total of 17 (seventeen) participants were interviewed and 13 (thirteen) of those were males and to ensure triangulation, 4 (four) females were interviewed. The interviews were semi-structured and the probing questions allowed for a deeper understanding of the phenomena. The interviews were transcribed and analysed using the conventional content analysis method where each transcript was read from beginning to end and the data was read word for word to determine the initial codes. The research found that coaching is in its infancy or emerging stages in Nigeria and there are male executives who would be uncomfortable working with female coaches. Both positive and negative gender stereotypes against women surfaced in the research as key contributors to the coach-matching process. The motherly nature of women, their general warmness, their meticulousness when approaching issues, their ability to be friendly and open and the fact that women are seen as having less ego are positive gender stereotypes that would encourage male executives to secure the services of female coaches. The findings also points out the gender stereotypes that could inhibit the formation of a coaching relationship and most of these stereotypes are found to be perpetuated by the applicable religion, tradition and customs within Nigeria.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Business and Executive Coaching February, 2017
Keywords: Leadership--Nigeria; Executive coaching--Nigeria; Women executives--Nigeria; Sex role in the work environment--Nigeria